Louis Hjelmslev and the Baltic countries - Vykypěl, Bohumil (Vilnius University Open Series, 2021)
This paper deals with texts by Louis Hjelmslev on Baltic topics, in particular an article from 1946 in which he defended the right of the Baltic countries to independence.
Keywords: Louis Hjelmslev; Baltic countries; structuralism; World War II; Soviet Union